Asurvey on the incidence of chronic suppurative otitis media(C.S.O.M) in Kermanian school children aged 12 to 15 years - K Mozafari-nia; M Hakakzadeh (Journal of Kerman University of Medical Sciences, 2000)
chronic suppurative otitis media(C.S.O.M) in a chronic infective and chronic inflammatory process of middle ear and mastoid that may be with or without cholesteatoma.Due to its significant problems and complications such as hearing loss,labyrinthitis,facial nerve paralysis,meningitis,brain abscess,extra and subdural  BSCESS AND LATERAL SINUS THROMBOSIS IS A FATAL AND IMPORTANT DISEASE.IN THIS STUDY 177-78(98-99) 3137 Kermanian school children aged 12 to 15 years from 174 schools were andomly checked for C.S.O.M Overage incidence rates of C.S.O.M was 5.7 per thousand,(female 0.5% and male 0.7%).Average of hearing loss was 25 db.there was no significant correlation between the incidence of C.S.O.M and underlying disease or factors such as sex,parental education and smoking(p>0.05)